Pengaruh Serpih Sampah Plastik (Pet) Pada Campuran Aspal Beton Dengan Pemanfaatan Buton Rock Asphalt Dan Liquid Asbuton - Daud Nawir (Borneo Engineering : Jurnal Teknik Sipil, 2022)
Asbuton is a natural asphalt material that has greater resilience and elasticity compared to extraction asphalt. When exposed to the sun and rain, asbuton has a strong and solid nature, the texture is also elastic so it is less likely to crack. One of the wastes that continues to be used in the field of road pavement is the plastic waste used in this research, which is the type of polyethylene terephthalate (PET). A lot of plastic waste is generated every year but little can be used. This research was attempted to identify the effect of the use of Buton Rock Asphalt (BRA) and plastic waste as a combination of Asphalt Concrete Layer (Laston) in terms of Marshall characteristics by using liquid asbuton and alteration of plastic accumulation content of 0%, 4%, 6%, and 8%. . The result achieved is that the accumulation of BRA and plastic waste flakes into the AC-WC asphalt concrete combination can reduce the use of asphalt by 8% by weight of asphalt with an optimum asphalt content value of 6.5%. The results of the characteristics of the AC-WC mixture with the addition of plastic waste flakes show the value of VIM decreases, VMA decreases, VFB increases with increasing effective asphalt content, Flow decreases, Stability will increase, Marshal Quotien (MQ) increases. Residual marshall stability values can be achieved above 90%, and voids in the mixture at refusal densities can be achieved in the range of greater than 2%.